Autophagy induction by xanthoangelol exhibits anti‐metastatic activities in hepatocellular carcinoma. (18th March 2019) - Yang, Xiuwei; Xie, Jing; Liu, Xiaoxiao; Li, Zichao; Fang, Kun; Zhang, Luying; Han, Mei; Zhang, Zhuang; Gong, Zhi; Lin, Xuezhu; Shi, Xianzhou; Gao, Hui; et al.
Abstract : Xanthoangelol (XAG), a prenylated chalcone isolated from the Japanese herb Angelica keiskei Koidzumi, has been reported to exhibit antineoplastic properties. However, the specific anti‐tumor activity of XAG in human hepatocellular carcinoma (HCC), and the relevant mechanisms are not known. Herein, we evaluated the effect of XAG against HCC in vitro and in vivo. Although XAG treatment did not significantly reduce the viability of the Hep3B and Huh7 cell lines, it suppressed cell migration, invasion, and EMT. This anti‐metastatic effect of XAG was due to induction of autophagy, because treatment with the autophagy inhibitor 3‐methyadenine (3‐MA) or knockdown of the pro‐autophagy Beclin‐1 effectively abrogated the XAG‐induced suppression of metastasis. Mechanistically, XAG induced autophagy via activation of the AMPK/mTOR signaling pathway, and XAG treatment dramatically increased the expression of p‐AMPK while decreasing p‐mTOR expression. In addition, blocking AMPK/mTOR axis with compound C abrogated the autophagy‐mediated inhibition of metastasis. The murine model of HCC metastasis also showed that XAG effectively reduced the number of metastatic pulmonary nodules. Taken together, our results revealed that autophagy via the activation of AMPK/mTOR pathway is essential for the anti‐metastatic effect of XAG against HCC. These findings not only contribute to our understanding of the anti‐tumor activity of XAG but also provide a basis for its clinical application in HCC. Before this study, evidence of XAG on HCC was purely anecdotal; present study provides the first comprehensive assessments of XAG on HCC metastasis and investigates its underlying mechanism. Results suggest that XAG exerts anti‐metastatic properties against HCC through inducing autophagy which is mediated by the activation of AMPK/mTOR signaling pathway. This research extends our knowledge about the antineoplastic properties of XAG and suggests that induction autophagy may represent future treatment strategies for metastatic HCC.